Bridget and the moose brothers - Lindenbaum, Pija (R & S Books, 2004)
Tells the story of Bridget who is tired of being an only child, but when she decides to try out as brothers some moose she finds sitting outside her building, she finds they don't turn out to be the sort of siblings she had in mind.